Altered circadian patterns of salivary cortisol in individuals with schizophrenia: A critical literature review. Issue 4 (November 2016) - Coulon, Nathalie; Brailly-Tabard, Sylvie; Walter, Michel; Tordjman, Sylvie
Abstract: This article focuses on stress vulnerability in schizophrenia through an integrated clinical and biological approach. The objective of this article is to better understand the relationships between vulnerability, stress and schizophrenia. First, the concept of vulnerability is defined and several models of vulnerability in schizophrenia are reviewed. Second, a section is developed on the biology of stress, and more specifically on the stress responses of the hypothalamo-pitutary adrenal (HPA) axis. Then, studies of cortisol circadian rhythms are summarized, suggesting hyper-reactivity of the HPA axis in patients with schizophrenia and high risk individuals for schizophrenia. The results support the models of stress vulnerability in schizophrenia and the hypothesis of high cortisol levels as an endophenotype in this disorder. In conclusion, this article highlights the interest of studying the cortisol circadian rhythms in schizophrenia and opens the perspective to identify high risk individuals for schizophrenia by measuring circadian patterns of salivary cortisol.